"We Can't Provide Season Tickets to the Opera": Staff Perceptions of Providing Preference-Based, Person-Centered Care. Issue 3 (26th May 2016) - Abbott, Katherine M.; Heid, Allison R.; Van Haitsma, Kimberly
ABSTRACT: Knowledge of a nursing home resident's everyday living preferences provides the foundation for ongoing individualized care planning. Objective: The purpose of this study is to identify nursing home (NH) staff perceptions of facilitators and barriers to learning about and meeting residents' preferences and reasons why staff feel residents change their minds about preferences. Methods: Focus group sessions and interviews were conducted with 36 NH staff members working in a facility that has been actively assessing resident preferences for five years. Results: Thematic codes classifying facilitators, barriers, and dependencies were identified. Staff shared ways they are able to help meet residents' preferences as well as barriers to fulfilling resident preferences through their own behaviors, facility characteristics, the social environment, and resident characteristics. In addition, staff believe that residents change their minds about important preferences 'depending on' several factors including; global environmental characteristics, social environment, resident characteristics, and general staff perceptions. Conclusions: This work identifies key facilitators and barriers to consider when implementing quality improvement efforts designed to improve the person-centered nature of care in nursing homes and is intended to further inform the culture change movement, which aims to transform NHs by empowering staff and delivering person-centered care.